Novel POSS-based organic–inorganic hybrid porous materials by low cost strategies1. Issue 12 (28th March 2015) - Wang, Shaolei; Tan, Liangxiao; Zhang, Chengxin; Hussain, Irshad; Tan, Bien
<x xml:space="preserve">Abstract</x> Two kinds of POSS-based organic–inorganic hybrid porous materials have been synthesized via Friedel–Crafts and Scholl coupling reactions, for the first time, using low-cost building blocks i.e., octaphenylsilsesquioxanes and simple knitting approaches to obtain high Brunauer–Emmett–Teller (BET) surface area porous polyhedral oligomeric silsesquioxane (POSS)-based hybrid materials.